Minat dan Penilaian Pembelian Produk Halal pada Masyarakat Lampung - Rahmawati, Wahyu; Supriyadi, Heri; Riswan (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
AbstractThis research emphasizes the importance of identifying factors that influence the decision to purchase halal certified cosmetics, such as halal labels, halal awareness, price and special offers. From the research results, it can be concluded that Lampung community students as a whole understand halal products according to Islamic teachings, but the choice of approach to halal and haram products is closely related to their religious beliefs and the community itself. However, in general, students want to increase their knowledge about halal products and the importance of following religious teachings. Lampung people also check and read whether the food has a halal certificate from a trusted party.Keywords: Interest, Assessment, Halal Products